A geographical approach to the risks of viral disease emergence in equatorial Africa - (:unkn) unknown (My University, 2012)
Through a geographical approach, we propose to contribute to the study of viral disease emergence in the equatorial African forestry by focusing on the probable original causes of the HIV-Aids virus. The Human immunodeficiency virus, responsible for the current Aids pandemic has zoonotic origins. Born from the recombination of several forms of simian retroviruses , the human virus (HIV) comes from the crossing of the inter-species barrier by viral agents carried by the primates (Simian Immunodeficiency Virus - VIS) and which have over time been selected and following multiple exposure s and extended to the human organisms. The subject of this work is treating the viral diseases emergence process as a system within which spatial dynamics, human aspects and environmental parameters interact. This requires exploring the origins of the emergence of HIV-aids, through the prism of a geographical study: migration, territorial, and domestic patterns of east Cameroonian forestry can create perilous situations in terms of exposure, diffusion and propagation of viral diseases
Keywords: African Research